PENGARUH METODE CIRC TERHADAP KETERAMPILAN MENULIS NARASI SISWA KELAS 5 SDN KAPUK JAYA KABUPATEN TANGERANG - Silvia Nur Hasanah; Yeni Nuraeni; Ahmad Amarullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to evaluate the influence of the CIRC method on the narrative writing skills of grade 5 students at SDN Kapuk Jaya, Tangerang Regency. The research method used is quantitative research with a quasi-experimental design. The research was conducted at SDN Kapuk Jaya, with data collection done through assessments of aspects such as the suitability of the story to the theme, the accuracy of the logical sequence of the story, the accuracy of the overall meaning of the story, word accuracy, sentence accuracy, spelling, and writing style. The validity of the research instrument was tested using item analysis with the Pearson Product Moment correlation. The reliability of the instrument was tested using the Alpha Cronbach technique. The results of the validity and reliability tests indicate that the instruments used in this research are valid and reliable. Hypothesis testing was done using one-sample mean difference test (T-Test) and independent two-sample mean difference test (T-Test). Based on the analysis, it was found that there is a significant difference in the narrative writing skills between students who use the CIRC method and those who do not. This indicates that the CIRC method can improve students' narrative writing skills. The findings of this research demonstrate that the CIRC method has a significant influence on the narrative writing skills of grade 5 students at SDN Kapuk Jaya, Tangerang Regency. The results of this research contribute significantly to the development of effective teaching methods to enhance students' narrative writing skills.